Nonthermal plasma (NTP) activated metal–organic frameworks (MOFs) catalyst for catalytic CO2 hydrogenation. Issue 4 (26th November 2019) - Chen, Huanhao; Mu, Yibing; Shao, Yan; Chansai, Sarayute; Xiang, Huan; Jiao, Yilai; Hardacre, Christopher; Fan, Xiaolei
Abstract: A systematic study of Ni supported on metal–organic frameworks (MOFs) catalyst (i.e., 15Ni/UiO‐66) for catalytic CO2 hydrogenation under nonthermal plasma (NTP) conditions was presented. The catalyst outperformed other catalysts based on conventional supports such as ZrO2, representing highest CO2 conversion and CH4 selectivity at about 85 and 99%, respectively. We found that the turnover frequency of the NTP catalysis system (1.8 ± 0.02 s −1 ) has a nearly two‐fold improvement compared with the thermal catalysis (1.0 ± 0.06 s −1 ). After 20 hr test, XPS and HRTEM characterizations confirmed the stability of the 15Ni/UiO‐66 catalyst in the NTP‐activated catalysis. The activation barrier for the NTP‐activated catalysis was calculated as 32 kJ mol −1, being lower than the activation energy of the thermal catalysis ( 70 kJ mol −1 ). In situ DRIFTS characterization confirmed the formation of multiple carbonates and formates on catalyst surface activated by NTP, surpassing the control catalysts (e.g., 15Ni/α‐Al2 O3 and 15Ni/ZrO2 ).